Separating the Words of a Language by Counting Factors - Saarela Aleksi (IOS PRESS, 2022)
For a given language L, we study the languages X such that for all distinct words u; v is an element of L, there exists a word x is an element of X that appears a different number of times as a factor in u and in v. In particular, we are interested in the following question: For which languages L does there exist a finite language X satisfying the above condition? We answer this question for all regular languages and for all sets of factors of infinite words.